Comparison of Crestal Bone Loss and Osteocalcin Release Kinetics in Immediately and Delayed Loaded Implants: A Randomized Controlled Trial. Issue 7 (8th March 2022) - Keshari, Rishabh; Chand, Pooran; Singh, Balendra P.; Jurel, Sunit K.; Singh, Ranjana; Singh, Punit Kumar; Solanki, Neeti
Abstract: Purpose: To compare concentration and release kinetics of osteocalcin and crestal bone loss under immediate and delayed loading conditions during osseointegration. Materials and methods: Forty‐one patients who were indicated for rehabilitation with dental implants randomly received either implant with placement of permanent prosthesis after 3 months (delayed loading) or implant with placement of permanent prosthesis within 7 days (immediate loading). Radiographic assessment of crestal bone loss at the mesial and distal surface was done at 3, 6, and 12 months after implant placement. Peri‐implant sulcular fluid was collected immediately from the buccal surface at two sites after implant insertion and also, at 7, 15, 30, and 90 days after surgery. The level of osteocalcin was evaluated using ELISA and data were compared using two sample t‐test. Differences between two groups were analyzed by unpaired Student's t test. Intragroup comparison was done by repeated measures ANOVA. Results: Mean crestal bone loss was lower in the immediate loading group compared to the delayed loading group at 3, 6, and 12 months ( p < 0.001). Intragroup comparison revealed a statistically significant increase in osteocalcin levels in both group I (delayed loading) (F = 26712.2) and group II (immediate loading) (F = 10497.2) at the predetermined time intervals. Conclusions: Less crestal bone loss and early release of osteocalcin was found in the immediately loaded group than in the delayed loaded group. The study substantiates that immediately loaded implants show less crestal bone as well as early release of osteocalcin facilitating upregulation of bone metabolism, improving long term health of bone and prognosis of implants. Immediately loaded implants can be a better treatment protocol provided there is adequate bone and primary stability.